IMPROVING STUDENTS’ WRITING ACHIEVEMENT THROUGH THE PROCESS GENRE APPROACH - Sri Wuri Handayani; Masitowarni Siregar (Universitas Negeri Medan, 2013)
This study attempts to Improving Students’ Achievement Through the Process GenreApproach. The objective of the study is to discover whether the use of the ProcessGenre approach could significantly improve students’ writing achievement. This studyconduct by applying Classroom Action Research which was carried out in two cycles inten meetings. The subject of this study of SMA Panca Budi Medan which consisted of39 students of class X – 2 reguler.. Orientation test was done in the first meeting, test IIwas done in the fourth meeting, and test III was done in the last meeting. The mean ofstudents’ score test III (76,242) was higher than the test II (66,878) and test I (57,606).Besides, the qualitative data was taken from observation sheet, interview, questionnaire,and diary notes. It was found that teaching learning process ran well. By applying theProcess Genre Approach in the classroom, the students understood the content ofdescriptive text easily. They also were active and enthusiastic during the teachinglearning process. The result of the research showed that the application of the ProcessGenre approach significantly improved students’ achievement in writing descriptive text